2006
DOI: 10.1038/sj.ejcn.1602556
|View full text |Cite
|
Sign up to set email alerts
|

Influence of methods used in body composition analysis on the prediction of resting energy expenditure

Abstract: Objective: There are considerable differences in published prediction algorithms for resting energy expenditure (REE) based on fat-free mass (FFM). The aim of the study was to investigate the influence of the methodology of body composition analysis on the prediction of REE from FFM. Design: In a cross-sectional design measurements of REE and body composition were performed. . In a normal range of FFM, REE predicted from FFM by different methods showed only small differences. The variance in REE explained by F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 27 publications
4
60
0
9
Order By: Relevance
“…Fat mass was assessed either by air-displacement plethysmography (BOD-POD Body Composition System, Life Measurement Instruments, Concord, CA, USA; n ¼ 4) or by hydrodensitometry (Borngässer Waagenbau, Grebbin, Germany; n ¼ 6) as described previously. 25,26 In a previous study, we had demonstrated a strong agreement between both methods in healthy young men (r ¼ 0.93). 26 calculated as the difference between body weight and fat mass.…”
Section: Anthropometric Measurements and Body Composition Analysismentioning
confidence: 99%
“…Fat mass was assessed either by air-displacement plethysmography (BOD-POD Body Composition System, Life Measurement Instruments, Concord, CA, USA; n ¼ 4) or by hydrodensitometry (Borngässer Waagenbau, Grebbin, Germany; n ¼ 6) as described previously. 25,26 In a previous study, we had demonstrated a strong agreement between both methods in healthy young men (r ¼ 0.93). 26 calculated as the difference between body weight and fat mass.…”
Section: Anthropometric Measurements and Body Composition Analysismentioning
confidence: 99%
“…Data obtained from large populations covering a wide weight range suggest that FFM is the major determinant of energy expenditure, explaining about 60-80% of its variance (Ravussin and Bogardus, 1989;Elia, 1992;Korth et al, 2007). The higher the FFM the higher is the REE.…”
Section: Functional Aspects Of Fat Mass and Ffmmentioning
confidence: 99%
“…FM was calculated from body volume (by air-displacement plethysmography), total body water (TBW by deuterium dilution), and bone mineral content (BMC by dual-energy X-ray absorptiometry) by using the equation of Fuller et al (35) A detailed description of each method and its precision was previously reported (36). FFM was calculated as the difference between body mass and FM.…”
Section: Four-compartment Modelmentioning
confidence: 99%